Utility of NISQ devices: optimizing experimental parameters for the fabrication of Au atomic junction using gate-based quantum computers - Kanezashi, Takumi; Tsukayama, Daisuke; Shirakashi, Jun-ichi; Shibuya, Tetsuo; Imai, Hiroshi (Applied physics express, 2025)
Feedback-controlled electromigration (FCE) enables precise regulation of atomic migration by carefully optimizing multiple experimental parameters. However, manually fine-tuning these parameters poses significant challenges. This study investigated the feasibility of autonomously fabricating Au atomic junctions through gate-based quantum computing using a noisy intermediate-scale quantum (NISQ) device, which effectively approximates solutions to combinatorial optimization problems. We compared the computational accuracy of the NISQ device against a previously reported D-Wave quantum annealer. The results indicate that the NISQ device achieved lower residual energies and produced higher-quality approximate solutions for large-scale problems than the quantum annealing system.